Impact of solar activity on Low Earth Orbiting satellites. (April 2020) - Khodairy, S; Sharaf, M; Awad, M; Abdel Hamed, R; Hussein, M
Abstract: In the present paper, we investigate the impact of solar activity on Low Earth Orbiting (LEO) satellites. How the increase in the number of coronal mass ejections and solar flares raises the likelihood that sensitive instruments in space and will be damaged by energetic particles accelerated in these events. So, we study the effect of perturbation forces on the Keplerian orbital elements of two LEO satellites using atmosphere model NRLMSISE00. The equation of motion and the effect of all perturbation are solved by using a High-Precision Orbit Propagation (HPOP) model, with Runge-Kutta 7 method, this method was treated by Cowell's technique. In this respect we deduce that solar activity influences the upper atmosphere; this influence is mediated through rapid geomagnetic disturbances.